Isolated traumatic brain injury as a cause of early coagulopathy – Case Report - Pires, Rafael Marques (Journal of the Portuguese Society of Anesthesiology, 2018)
Trauma induced coagulopathy has been reported in cases of isolated traumatic brain injury. We report a case where thromboelastometry (ROTEM®) was the only warning sign of the ensuing coagulopathy. A 77 years-old female, fell down multiple stairs. Assisted on scene, she was intubated and transported to the emergency department. Head computed tomography showed an acute subdural hematoma. No other trauma injury or signs of active bleeding were identified on admission, but a blood sample for ROTEM® was collected. During craniotomy she developed hemodynamic instability, as well as signs of coagulopathy. First ROTEM® showed absence of clot formation and transfusion therapy was started. There was clinical improvement, and a post-transfusion ROTEM® showed improved clot formation. Admitted to the Intensive Care Unit, the patient died 24 hours after the initial neurologic injury. Early identification of coagulopathy associated with trauma is crucial, which can contribute to an improved outcome.